2012
DOI: 10.1597/10-204
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Presentation of Columellar Features, Nostril Anatomy, and Alveolar Alignment in Bilateral Cleft Lip and Palate after Infant Orthopedics with and without Nasoalveolar Molding

Abstract: Infants who received NAM had longer columellae and better-aligned alveolar segments than those who received only IO. Other nostril dimensions were not significantly different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…When BCLP cleft subjects treated with NAM‐assisted surgery were compared to those treated with surgery alone there was evidence of significantly improved nasal morphology both in the short‐term and long‐term . More specifically, in BCLP infants, NAM was found to improve the nasal angle, improve nostril height and bialar width, correct columella deviation, lengthen and widen the columella, increase nasal tip protrusion and reduce alar base width . Also in BCLP infants, NAM was seen to increase prolabium length, force the protruded premaxillary segment into alignment with the dental alveolar segments, improve the shape of the maxillary arch, help align the alveolar segments and reduce cleft width before surgery .…”
Section: Discussionmentioning
confidence: 96%
“…When BCLP cleft subjects treated with NAM‐assisted surgery were compared to those treated with surgery alone there was evidence of significantly improved nasal morphology both in the short‐term and long‐term . More specifically, in BCLP infants, NAM was found to improve the nasal angle, improve nostril height and bialar width, correct columella deviation, lengthen and widen the columella, increase nasal tip protrusion and reduce alar base width . Also in BCLP infants, NAM was seen to increase prolabium length, force the protruded premaxillary segment into alignment with the dental alveolar segments, improve the shape of the maxillary arch, help align the alveolar segments and reduce cleft width before surgery .…”
Section: Discussionmentioning
confidence: 96%
“…According to the systematic review published, there was evidence on the improvement of nasal symmetry in UCLP patients using NAM appliances. [102] Similarly, Suri et al, [65] reported that infants who received NAM presented more symmetric and more ideal alveolar segment approximation, a straighter columella, and greater columellar length than those who received IO only. Shetty et al [103] reported that cleft infants treated with NAM appliance within 1 month of life showed improvement in nasal dome height, columellar height and resembled non cleft patients at 18 months of age.…”
Section: Discussionmentioning
confidence: 96%
“…This parameter is nevertheless known to be positively influenced by NAM treatment, especially in cases of BCLP. 11 , 27 Suri et al 29 reported that infants who received NAM therapy had longer columella and better-aligned alveolar segments than those who received only feeding plate therapy. In their study, other nostril dimensions were not significantly different, comparable to our results.…”
Section: Discussionmentioning
confidence: 99%